The international handbook on social innovation collective action, social learning and transdisciplinary research - Moulaert, Frank; Edward Elgar Publishing (Cheltenham : Edward Elgar Pub. Ltd., 2013)
The challenges of poverty and social exclusion cannot be fully resolved through conventional public sector policies and market-led innovation. The case studies in this Handbook capture some of the key success factors of socially innovative action in different socio-economic contexts. This Handbook will inspire readers as it highlights the creativity and commitment of diverse enterprises and movements working for social innovation. Anna Kajumulo Tibaijuka, Minister for Lands, Housing and Human Settlements, United Republic of Tanzania, and retired UN Under Secretary General, immediate former Executive Director of UN-HABITATSocial innovation may not be a new idea but it is clearly an idea whose time has come, not least because the traditional models of innovation narrowly framed technical models have run their course and no longer resonate in a world of societal challenges. This Handbook has two great merits it brings conceptual rigour to the debate and it provides compelling narratives of social innovation in practice. Kevin Morgan, Cardiff University, UK In an era where social innovation is re-emerging as an important policy framework for bringing social transformation, this volume is a significant contribution to the theory and practice of social innovation. The incremental discussion from concepts to theory to practice and then to social innovation research is supported by cases literally from all over the globe. It moves the discourse from isolated models of neighbourhood engagements and social enterprises, to a comprehensive, multidimensional approach combining needs, social relations and empowerment. A must read for academicians, learners, practitioners and policy makers alike. S. Parasuraman, Tata Institute of Social Sciences, Mumbai, India Social innovation is an important instrument for understanding how contemporary societies deal with social change and how social practices and policies intended to combat poverty and social exclusion are developed and implemented effectively. The Handbook offers a valuable contribution to the development of a clear, transdisciplinary and critical understanding of social innovation practices. The reader will find an in-depth discussion of the most important theoretical approaches to the concept and a thorough exposition of the epistemological and methodological framework for research in social innovation. The volume includes a number of interesting case studies in different areas of social change and issues of policy and governance. Enzo Mingione, University of Milano-Bicocca, ItalyThis enriching Handbook covers many aspects of the scientific and socio-political debates on social innovation today.The contributors provide an overview of theoretical perspectives, methodologies and instructive experiences from all continents, as well as implications for collective action and policy. They argue strongly for social innovation as a key to human development. The Handbook defines social innovation as innovation in social relations within both micro and macro spheres, with the purpose of satisfying unmet or new human needs across different layers of society. It connects social innovation to empowerment dynamics, thus giving a political character to social movements and bottom-up governance initiatives. Together these should lay the foundations for a fairer, more democratic society for all.This interdisciplinary work, written by scholars collaborating to develop a joint methodological perspective toward social innovation agency and processes, will be invaluable for students and researchers in social science and humanities. It will also appeal to policy makers, policy analysts, lobbyists and activists seeking to give inspiration and leadership from a social innovation perspective.
pt. I. Social innovation : from concept to theory and practice -- pt. II. Social innovation theory : its role in knowledge building -- pt. III. Instructive case studies in social innovation analysis -- pt. IV. Social innovation analysis : methodologies -- pt. V. Collective action, institutional leverage and public policy -- pt. VI. Frontiers in social innovation research.
Includes bibliographical references and index.
Keywords: Social movements; Electronic books